1990
DOI: 10.1002/bjs.1800771228
|View full text |Cite
|
Sign up to set email alerts
|

Early tracheostomy for primary airway management in the surgical critical care setting

Abstract: MECHANICAL VENTILATION REQUIRING cannulation of the trachea is an integral part of the therapy provided to patients in the surgical critical care setting. In the 1950s and early 1960s, airway management consisted of a short period of translaryngeal intubation quickly converted to tracheostomy. In the late 1960s and 1970s the time of translaryngeal intubation before tracheostomy gradually increased with the development of improved endotracheal tube design and construction. This concept became the standard of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
228
0
17

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(249 citation statements)
references
References 14 publications
4
228
0
17
Order By: Relevance
“…Patients with C-SCI are at increased risk of respiratory failure that may lead to the need for tracheostomy [6,11,13,15,21]. Pulmonary complications are the most common complications in patients with C-SCI [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with C-SCI are at increased risk of respiratory failure that may lead to the need for tracheostomy [6,11,13,15,21]. Pulmonary complications are the most common complications in patients with C-SCI [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with respiratory failure after C-SCI will require intubation and mechanical ventilation, leading to tracheostomy. It has been reported that 21-77 % of patients with C-SCI have undergone tracheostomy [6,11,13,15,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations